SARS-COV-2 PREVALENCE IN INDIA COMPARED TO THE REST OF THE GLOBE AND ASCERTAINS EPIDEMIOLOGICAL CHARACTERISTICS ASSOCIATED WITH THE COVID-19 PANDEMIC DURING 2020 IN INDIA - M. Rajesh Kumar Rao; Rabindra N. Padhy; Manoj Kumar Das (Sabiad)
Objectives: SARS-CoV-2 triggers a pandemic of COVID-19. We ascertain the pandemic burden of COVID-19 disease between India and the rest of the world; monitor the burden of COVID-19 disease in Indian states and union territories compared to other countries with nearly equivalent population sizes, and study the epidemiological characteristics.Material and Methods: A population-based comparative optimization algorithms study was conducted on all COVID positive cases reported by 31st December 2020.Results: Confirmed cases resulted in India with a ratio of 1:7.2 to the rest of the world, with a lower mortality rate with a ratio of 1:12 (CMR per 100,000 people) than other countries. Many Indian administrative regions have lower morbidity rates (Z-values range from -2653.7369 to -11.6403) and mortality (Z-values range from -439.446 to -4.86) than the countries selected. In India, 184,728,001 tests were done, with 5.6% cases confirmed, 96.1% recovered, and 1.4% dying due to COVID-19. COVID-19 was more prevalent in males and patients aged 25–44, whereas SARSCoV- n2 killed the most people over the age of 60. Bihar had the most cases of infection, while Punjab had the most deaths.Conclusion: SARS-CoV-2 disease led India to have a lower morbidity and mortality burden than the rest of the world. The pandemic curves of COVID-19 resulted in daily peaks most significantly, and the cumulativennumber of cases increased tremendously with an upward trend. Analytical, spatial, and temporal research studies will be carried out to understand the effect of climate change and indicators that correlate with the epidemiological characteristics of the emerging coronavirus.